Desafios e atuação docente na sala de recursos multifuncionais em uma escola da rede pública estadual da cidade de Tocantinópolis - TO - Sousa, Dalila Morais de (Universidade Federal do Tocantins, 2022)
The present research aims to investigate the challenges of teachers who work in the Multifunctional Resource Room and to know how this space is organized for the development of didactic-pedagogical activities in the context of a State Public School in the city of Tocantinópolis, in Tocantins. The development of this study was based on the theoretical perspective of Special Education and Inclusive Education, a field of knowledge that has been breaking with a trajectory of exclusion and segregation of people with disabilities. The research, with a qualitative approach, was guided by the theoretical perspective of Inclusive Education. The generation of data was based on interviews with the teachers of the school participating in the research and on the analysis of documents that guide the didactic work in the school. With the development of this study, we know the professional life trajectories of teachers who work in the Multifunctional Resource Room and, from the point of view of these teachers, we observe several challenges faced by them in the school routine. In addition, in the teachers' statements, it was possible to notice methodological strategies used by them, which allowed us to notice that the didactic-pedagogical work in the Inclusive Education bias is complex and demands creative professionals committed to educational praxis and to their training in The reason why the service involves students with different types of special needs, which leads the teachers to work with each student in a specific way. We conclude that, in the investigated school, the teachers reveal difficulties in achieving inclusion and work from the point of view of integration, this because there are students who are not fully attended to in their needs, either due to the lack of teaching material or the absence of a qualified professional to accompany the student in the regular classroom, which prevents the student from actually being included.